Immunogenicity, safety and reactogenicity of heterologous (third dose) booster vaccination with a full or fractional dose of two different COVID-19 vaccines: A phase 4, single-blind, randomized controlled trial in adults - Costa Clemens, SA; Marchevsky, N; Kelly, S; Felle, S; Eldawi, A; Rajasingam, R; Mahmud, R; Lambe, T; Voysey, M; Gonzalez, I; Milan, EP; Justino, MC; et al. (Taylor and Francis, 2023)
In this phase 4 study we assessed boosting with fractional doses of heterologous COVID-19 vaccines in Brazilian adults primed with two doses of CoronaVac (Sinovac/Butantan, São Paulo, Brazil) at least 4 months previously. Participants received either full-dose of ChAdOx1-S (Group 1, n = 232), a half dose of ChAdOx1-S (Group 2, n = 236), or a half dose of BNT162b2 (Group 3, n = 234). The primary objective was to show 80% seroresponse rates (SRR) 28 d after vaccination measured as IgG antibodies against a prototype SARS-CoV-2 spike-protein. Safety was assessed as solicited and unsolicited adverse events. At baseline all participants were seropositive, with high IgG titers overall. SRR at Day 28 were 34.3%, 27.1% and 71.2%, respectively, not meeting the primary objective of 80%, despite robust immune responses in all three groups with geometric mean-fold rise (GMFR) in IgG titers of 3.39, 2.99 and 7.42, respectively. IgG immune responses with similar GMFR were also observed against SARS-CoV-2 variants, Alpha, Beta, Delta, Gamma and D614G. In subsets (n = 35) of participants GMFR of neutralizing immune responses against live prototype SARS-CoV-2 virus and Omicron BA.2 were similar to the IgG responses as were pseudo-neutralizing responses against SARS-CoV-2 prototype and Omicron BA.4/5 variants. All vaccinations were well tolerated with no vaccine-related serious adverse events and mainly transient mild-to-moderate local and systemic reactogenicity. Heterologous boosting with full or half doses of ChAdOx1-S or a half dose of BNT162b2 was safe and immunogenic in CoronaVac-primed adults, but seroresponse rates were limited by high baseline immunity.